Efektivitas Humas dan Wartawan dalam Menyosialisasikan Program Website Layanan Aspirasi Diskominfo Labuhan Batu - Sakti Tambak, Ahmad Budi; Saragih, M. Yoserizal; Abidin, Syahrul (IAI Nasional Laa Roiba Bogor, 2024)
Communication is a need that cannot be separated from humans. In the develop of mass communication there was a development regarding mass media when the internet was discover. The aim to achieved through this research is: